Correlation between clinical parameters of crown and gingival morphology of anterior teeth and periodontal biotypes - Yin, Xiao-jie (BMC Oral Health, 2020)
BACKGROUND: In this study, we conducted a quantitative analysis of the clinical parameters of crown and gingival morphology (CGM) of the maxillary anterior teeth (MAT). We also analyzed the correlation of these parameters with periodontal biotype (PB), with a view to providing objective standards for PB diagnosis. METHODS: The three-dimensional (3D) maxillary digital models of 56 individuals were obtained using an intra-oral scanner. The following parameters were measured with the SpaceClaim software: gingival angle (GA), papilla width (PW), papilla height (PH), crown length (CL), crown width (CW), crown width/crown length ratio (CW/CL), bucco-lingual width of the crown (BLW), contact surface width (CSW), and contact surface height/crown length ratio (CS/CL). The PB were determined based on the transparency of the periodontal probe through the gingival sulcus. Independent factors influencing PB were analyzed by logistic regression, and the optimal cutoff values for the independent influencing factors were analyzed using receiver operating characteristic curves (ROC curves). RESULTS: There was no significant difference in the parameters of CGM of the MAT at the left and right sides. The thick biotype accounted for 69.6%, and the parameters of GA, PW, PH, CW, CW/CL and CS/CL were significantly correlated with PB (P ≤ 0.2). GA (odds ratio (OR) = 1.206) and PW (OR = 5.048) were identified as independent predictive factors of PB, with areas under the ROC curve (AUC) of 0.807 and 0.881, respectively, and optimal cutoff values of 95.95° and 10.01 mm, respectively. CONCLUSION: The CGMs of the MAT at the left and right side are symmetrical. The thin biotype accounts for a small proportion, and GA and PW are independent influencing factors of PB. GA of 95.95° and PW of 10.01 mm are the optimal cutoff values for categorization of individuals as thick biotype. This indicates that when the GA and PW of the right maxillary central incisor are G ≥ 95.95° and ≥ 10.01 mm, respectively, there is a higher probability that these individuals will be categorized as thick biotype.